A new record Species for Flora of Vietnam – Curcuma singularis Gagnep. (Zingiberaceae) - Nguyen, Binh Quoc; Hoang, Tuan Anh; Nguyen, Dat Van; Tran, Thanh Thi Viet; Nguyen, Hanh Phuong; Nguyen, Cuong Manh; Nguyen, Thanh Trung (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 1, 2017)
Curcuma singularis Gagnep., a new record species from the Central Highlands (Gia Lai prov., KBang dist.) is described and illustrated with pictures, and compared to some species in the same group "Ecomata", together with a species with similar morphological characteristics from another group: Curcuma cochinchinensis . The species C. singularis is known by locals as Cay khoe or Sam da, and its rhizomes are used by in habitants to help them improve health.